Air Medical Transportation for Severe Acute Pancreatitis Patients over an Extra Long Distance: Is It Safe Enough? - Lin Gao; Jingzhu Zhang; Kun Gao; Yiyuan Pan; Xiaotao Qin; Jie Zhang; Jing Zhou; Guotao Lu; Weiqin Li; Zhihui Tong (Gastroenterology Research and Practice)
Objective. Severe acute pancreatitis (SAP) patients usually develop persistent organ dysfunction which causes the majority of deaths. It is important for SAP patients to receive centralized diagnosis and treatment in an experienced tertiary center. China, as a vast country with uneven distribution of medical resources, should take advantage of air medical transportation to meet the challenge of patient transfer among different regions. The aim of this study was to evaluate the safety and effectiveness of air transport for SAP patients via extra long distance. Methods. This was a retrospective analysis of all air medical transportations for SAP patients admitted to Jinling Hospital from January 2010 to December 2016. The general characteristics, transportation process, and clinical outcomes of these patients were recorded, and the safety and effectiveness of air transport were evaluated. Results. All the 20 SAP patients were successfully transferred by chartered aircraft without any occurrence of severe transport-associated complications. The mean transport time was 5.86 hours and the average transport distance was 1530 kilometers. The majority of SAP patients got timely intervention and the ultimate mortality rate was 15%. Conclusions. Air medical transport appears to be safe and effective for SAP patients with vital organ dysfunctions during the extra long-distance transportation.